Some l(p)-Type New Sequence Spaces and Their Geometric Properties - Savas, Ekrem; Karakaya, Vatan; Simsek, Necip (HINDAWI PUBLISHING CORPORATION, 2009)
We introduce an l(p)-type new sequence space and investigate its some topological properties including AK and AD properties. Besides, we examine some geometric properties of this space concerning Banach-Saks type p and Gurarii's modulus of convexity. Copyright (C) 2009 Ekrem Savas, et al.
Keywords: MATRIX TRANSFORMATIONS; Mathematics